2019
DOI: 10.1177/1556984519845657
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Echocardiographic Outcomes After Aortic Valve Repair Surgery

Abstract: Objective To assess early and late clinical outcomes in patients who underwent aortic valve repair surgery for aortic valve insufficiency, and to investigate predictors for recurrence. Methods Of 151 consecutive patients who underwent aortic valve repair surgery for varying degrees of aortic insufficiency (AI) in our department between 2004 and 2018, 60 (40%) underwent aortic root replacement, 71 (47%) aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Although none of the individuals in our study group had a persistent ductus arteriosus, our meta-analysis identified a rate of 3.3% in bicuspid aortic valve disease. However, the number of children was high in studies that support a high prevalence of persistent ductus arteriosus (39,50), whereas collectives with age ranges similar to ours showed a prevalence of 1.3% (37,52). Atrial septal defect is diagnosed with a 0.016% prevalence (1.64/10,000 live births) worldwide (60).…”
Section: Discussionsupporting
confidence: 53%
“…Although none of the individuals in our study group had a persistent ductus arteriosus, our meta-analysis identified a rate of 3.3% in bicuspid aortic valve disease. However, the number of children was high in studies that support a high prevalence of persistent ductus arteriosus (39,50), whereas collectives with age ranges similar to ours showed a prevalence of 1.3% (37,52). Atrial septal defect is diagnosed with a 0.016% prevalence (1.64/10,000 live births) worldwide (60).…”
Section: Discussionsupporting
confidence: 53%
“…As to BAV patients, Aicher et al [ 27 ] report 5-year freedom from the reintervention rate of 88% and the 10-year rate of 81%, whereas Ram et al [ 28 ] identify BAV as an independent risk factor for reintervention. In the TAV patients, our results are similar to those published by de Kerchove et al [ 25 ], who report freedom from reintervention of 92 ± 5%.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical decision or management strategies were subsequently based on the aortic dilatation classifications [5,6]. Recommendations for the surgical management of dilatation and aneurysm of the ascending aorta in cases of BAV associated aortopathy are clearly stated in the treatment guidelines but still void of specifics [7,8]. This method basically involves resection and replacement of the aneurysmal aorta with a vascular graft.…”
Section: Introductionmentioning
confidence: 99%